2020
DOI: 10.11604/pamj.2020.36.190.21072
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and left ventricular hypertrophy in hypertensive patients in Ado-Ekiti

Abstract: Introduction systemic hypertension is a foremost risk factor for cardiovascular morbidity and mortality. Its actions are manifested on organs like the brain, heart and kidneys. High serum uric acid (SUA) escalates cardiovascular vulnerability in patients with systemic hypertension. Methods a cross-sectional study was performed in 271 (178 females, 93 males) patients with systemic hypertension. Two hundred and seventy one healthy age and sex matched non-hypertensive pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…23 However, in the condition of accompanying with other basic diseases such as hypertension, atrial fibrillation, and type 2 diabetes, HUA accelerates cardiac hypertrophy with no obvious EF change. 24 27 Consistently, our heart weight data also showed an enlarged heart with limited parameter impairment. Echocardiography examination indicated that the modeling method mainly influenced the ventricular end in the diastolic stage but not in the systolic stage.…”
Section: Discussionsupporting
confidence: 84%
“…23 However, in the condition of accompanying with other basic diseases such as hypertension, atrial fibrillation, and type 2 diabetes, HUA accelerates cardiac hypertrophy with no obvious EF change. 24 27 Consistently, our heart weight data also showed an enlarged heart with limited parameter impairment. Echocardiography examination indicated that the modeling method mainly influenced the ventricular end in the diastolic stage but not in the systolic stage.…”
Section: Discussionsupporting
confidence: 84%
“…TDM is also employed for the evaluation of adherence among patients with chronic diseases on the African continent. Recently, Adewuya et al [138] investigated the use of serum uric acid levels as a marker for predicting medication adherence. In their study, they utilized both the MMAS-8 scale and levels of uric acids among hypertensive patients and concluded that there was a linear relationship between higher levels of uric acid and the percentage of increasing nonadherence to the medications; therefore, serum markers can be used as a measure of medication adherence.…”
Section: Therapeutic Drug Monitoring Utilizing Plasma and Urine Samplesmentioning
confidence: 99%